2020
DOI: 10.1681/asn.2019060623
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3, Randomized, Double-Blind, Active-Comparator (Darbepoetin Alfa) Study of Oral Roxadustat in CKD Patients with Anemia on Hemodialysis in Japan

Abstract: BackgroundRoxadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor approved in China for dialysis-dependent CKD anemia.MethodsThis phase 3, 24-week, double-blind, double-dummy study evaluated roxadustat’s noninferiority to darbepoetin alfa for hemodialysis-dependent CKD anemia. We randomly assigned Japanese patients to oral roxadustat three times weekly or to darbepoetin alfa injections once weekly, titrating doses to maintain hemoglobin between 10–12 g/dl. The primary end point was change o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
213
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(244 citation statements)
references
References 17 publications
(31 reference statements)
12
213
0
1
Order By: Relevance
“…In a US study, cerebrovascular accident (1.9%) and complex partial seizure (0.9%) occurred after 19 weeks of roxadustat in ESKD patients receiving maintenance HD, and such adverse events were not observed in the epoetin alfa group 47 . Cerebral infarction (0.7%) was also reported in a study of Japanese population after 24 weeks treatment with roxadustat compared to none in the darbopoietin alfa group 79 . One study reported that vadadustat treatment in NDD CKD patients was associated with slightly higher incidence of headache and dizziness compared with placebo during the 20 weeks of treatment 42 .…”
Section: Potential Concerns Of Hif‐phimentioning
confidence: 87%
See 1 more Smart Citation
“…In a US study, cerebrovascular accident (1.9%) and complex partial seizure (0.9%) occurred after 19 weeks of roxadustat in ESKD patients receiving maintenance HD, and such adverse events were not observed in the epoetin alfa group 47 . Cerebral infarction (0.7%) was also reported in a study of Japanese population after 24 weeks treatment with roxadustat compared to none in the darbopoietin alfa group 79 . One study reported that vadadustat treatment in NDD CKD patients was associated with slightly higher incidence of headache and dizziness compared with placebo during the 20 weeks of treatment 42 .…”
Section: Potential Concerns Of Hif‐phimentioning
confidence: 87%
“…We reviewed published placebo or competitor‐controlled trials of six HIF‐PH inhibitors in DD and NDD CKD patients. The pooled incidence of thrombotic side effects by HIF‐PHI according to the status of CKD status were summarized in Table 6 and 4B 14,21‐23,37‐44,46‐51,79 . In DD patients, the incidence of CV events was low (42/1741 [2.4%]).…”
Section: Potential Concerns Of Hif‐phimentioning
confidence: 99%
“…This is reflected in the increased effective t 1/2 in subjects with severely impaired kidney function or with ESRD on HD/HDF compared with those with normal kidney function. For drugs with multicompartmental kinetics such as roxadustat, the effective t 1/2 is considered a more appropriate parameter than t 1/2 to predict drug accumulation [ 19 ]. Since the effective half-life considers the entire plasma concentration–time profile of the drug, it may better reflect total clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The following is in response to a letter to the editor submitted by Tanaka et al concerning the recently published article titled "Phase 3, Randomized, Double-Blind, Active-Comparator (Darbepoetin Alfa) Study of Oral Roxadustat in CKD Patients with Anemia on Hemodialysis in Japan." 1 In their letter, Tanaka et al cite several concerns regarding the effects of roxadustat versus darbepoetin alfa (DA) in patients with inflammation, defined according to highsensitivity C-reactive protein (hs-CRP). The specific concerns cited by Tanaka et al are as follows: (1) that the study did not aim to compare the efficacy of study drugs in patients with inflammation, and the small sample of patients with high hs-CRP will not allow for further statistical analysis; (2) that the changes in hs-CRP during the treatment period were not considered; (3) that, in patients with high hs-CRP, the hemoglobin (Hb) levels during the evaluation period in the DA group seemed slightly higher than those in the roxadustat group; and (4) that, in the study, the mean Hb level and the rate of increase in Hb at week 4 were higher in the roxadustat group than in the DA group.…”
Section: Authors' Replymentioning
confidence: 99%